«Blood cannot lie». Between a genetic-strategic conception of territory and a relational way of seeing the world - Volpi, Laura (2021)
Kichwa indigenous people of the Peruvian Amazon Forest are facing a territorial conflict due to the establishment of a Regional Conservation Area on their homelands. In order to question the legitimacy of native claims, the Regional Government puts forward the hypothesis of the Andean kichwa migration. On the other hand, several cultural mediators hope to help this native people, using some biomolecular investigations (Sandoval et al., 2016; Barbieri et al., 2017) that «scientifically» certify its ancestral relationship with the surrounding territories. This article wants to examine the existing misunderstandings about the concepts of «ancestry» and «territory» whose meaning, in the native sphere, overcomes limits imposed by national jurisdiction and legal terminology. Despite having assimilated an ancestral-genetic discourse, several indigenous leaders reshape it in light of a native conception of territory, perceived as a complex network of present and active relationships between living people and ancestors.